Comprendre et intervenir sur le stress au travail : une étude de cas - Emmanuel Poirel; Frédéric Yvon (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article presents a case study using stimulated recall by selfconfrontation based on the emotional-transactional model of stress. The detailed and specific analysis of an incident in a railway company shows that stress is more an experience of powerlessness. Therefore, it highlights a traditional distortion of the transactional model used to legitimate psycho-organizational interventions focused on the individual. Thus, on the basis of this case study, it is possible to link stress and pathological consequences to anxiety by showing the consequences relating to the perception of having few resources to cope with the situation.